Risk Preference and Entrepreneurial Investment at the Top of the Wealth Distribution - Frank M. Fossen; Johannes König; Carsten Schröder (Institute of Labor Economics (IZA), 2020)
We present first evidence how individual risk preferences shape entrepreneurial investment among the very wealthy using novel survey data from the top of the wealth distribution, which have been added to the 2019 German Socio-economic Panel Study. The data include private wealth balance sheets, in particular the value of own private business assets, and a standard measure of risk tolerance. We find that wealthy individuals are more likely to be entrepreneurs and invest a larger share of their wealth in their own businesses when they are more willing to take risks. These associations are stronger among wealthy than among less wealthy individuals. The results imply that policies affecting the riskiness of income and wealth, such as tax policy and bankruptcy law, affect risky investment decisions at the top of the wealth distribution in ways strongly determined by individual risk tolerance. Since the wealthy dominate aggregate risky investment, their risk preferences must be taken into account for theory development, empirical analysis, and policy evaluations.
Keywords: J22; J23; L26; D14; 330; wealth; entrepreneurship; risk; portfolio choice